2019
DOI: 10.1177/2158244019885146
|View full text |Cite
|
Sign up to set email alerts
|

Causal Relation Between Stock Market Performance and Firm Investment in China: Mediating Role of Information Asymmetry

Abstract: The main objectives of this study are to examine the impact of stock price performance on firm’s investment and to investigate the counter impact of changes in investment expenditures on stock price performance. The random effects model was applied on the panel data of Chinese manufacturing firms listed at the Shanghai Stock Exchange and the Shenzhen Stock Exchange during the period 2002 to 2016. The sample contains 398 firms with 5,970 observations. Although there is a statistically significant and negative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Some prior studies (e.g., Chandrakumaramangalam and Govindasamy, 2010;Xin and Xu, 2012;Grazzi et al, 2016;Taipi and Ballkoci, 2017;Lian et al, 2017;Korent and Orsag, 2018;Singh and Bagga, 2019) found a positive association between investments and profitability. In contrast, other prior studies (e.g., Shima, 2010;Alipour et al, 2015;Zaigham et al, 2019;Bialowolski and Wezia, 2014;Reschiwat et al, 2020) found a negative association among different types of investments and profitability. These contrasting findings motivated us to study the relationship between a firm's investment intensity and EBITDA with special reference to companies in GCC countries.…”
mentioning
confidence: 66%
“…Some prior studies (e.g., Chandrakumaramangalam and Govindasamy, 2010;Xin and Xu, 2012;Grazzi et al, 2016;Taipi and Ballkoci, 2017;Lian et al, 2017;Korent and Orsag, 2018;Singh and Bagga, 2019) found a positive association between investments and profitability. In contrast, other prior studies (e.g., Shima, 2010;Alipour et al, 2015;Zaigham et al, 2019;Bialowolski and Wezia, 2014;Reschiwat et al, 2020) found a negative association among different types of investments and profitability. These contrasting findings motivated us to study the relationship between a firm's investment intensity and EBITDA with special reference to companies in GCC countries.…”
mentioning
confidence: 66%
“…Using returns data of US-listed security, from July 1963 to December 2001, Hou and Moskowitz (2005) found that high information asymmetry corresponds to increased price delay. Recently, in China Zaigham et al (2019) show that information asymmetry, measured using the interaction terms of stock prices and asymmetric information (measured by firm age and size) and stock prices are negatively and significantly related. It is expected that stock price is positively related to the proxies of information asymmetry.…”
Section: Context Methodology and Methodsmentioning
confidence: 99%
“…Empirical research provides mixed results regarding the relationship between information asymmetry and stock price. Some prove that stock price is positively associated with the bid-ask spread (Yoon et al, 2011;Kuo and Lin, 2014;Hou and Moskowitz, 2005), while others prove the opposite (Heflin et al, 2005;Gajwiski and Li, 2015;Zaigham, et al, 2019). Using returns data of US-listed security, from July 1963 to December 2001, Hou and Moskowitz (2005) found that high information asymmetry corresponds to increased (2019) show that information asymmetry, measured using the interaction terms of stock prices and asymmetric information (measured by firm age and size) and stock prices are negatively and significantly related.…”
Section: Stock Price (Lnprice)mentioning
confidence: 99%
“…In addition, large firms have the economies of scale to attract more investment and by extension increase the firm's market share price. Firm size has been measured in different ways to include volume of traded shares (Zaigham,Wang & Ali, 2019), value of total assets, number of employees, and market capitalization (Leledakis, Davidson & Smith, 2004).The study of Llorente, Michaely, Saar and Wang (2002) posited that average daily number of shares traded increase with firm size.…”
Section: Figure 1 Source: Field Work (2020)mentioning
confidence: 99%